Influence of erythrocyte aggregation on radial migration of platelet-sized spherical particles in shear flow. (16th August 2017) - Guilbert, Cyrille; Chayer, Boris; Allard, Louise; Yu, François T.H.; Cloutier, Guy
Abstract: Blood platelets when activated are involved in the mechanisms of hemostasis and thrombosis, and their migration toward injured vascular endothelium necessitates interaction with red blood cells (RBCs). Rheology co-factors such as a high hematocrit and a high shear rate are known to promote platelet mass transport toward the vessel wall. Hemodynamic conditions promoting RBC aggregation may also favor platelet migration, particularly in the venous system at low shear rates. The aim of this study was to confirm experimentally the impact of RBC aggregation on platelet-sized micro particle migration in a Couette flow apparatus. Biotin coated micro particles were mixed with saline or blood with different aggregation tendencies, at two shear rates of 2 and 10 s −1 and three hematocrits ranging from 20 to 60%. Streptavidin membranes were respectively positioned on the Couette static and rotating cylinders upon which the number of adhered fluorescent particles was quantified. The platelet-sized particle adhesion on both walls was progressively enhanced by increasing the hematocrit ( p  < 0.001), reducing the shear rate ( p  < 0.001), and rising the aggregation of RBCs ( p  < 0.001). Particle count was minimum on the stationary cylinder when suspended in saline at 2 s −1 (57 ± 33), and maximum on the rotating cylinder at 60% hematocrit, 2 s −1 and the maximum dextran-induced RBC aggregation (2840 ± 152). This fundamental study is confirming recent hypotheses on the role of RBC aggregation on venous thrombosis, and may guide molecular imaging protocols requiring injecting active labeled micro particles in the venous flow system to probe human diseases.